The Hukou Impact on the Chinese Wage Structure - Christian Dreger; Yanqun Zhang (Institute of Labor Economics (IZA), 2017)
Faster urbanization plays a key role in the Chinese economic transformation. However, at the Lewis turning point, the hukou institution constitutes a serious risk to the process, as it restricts the access of migrants to public services offered by cities. To attract further migration, firms started to accept a premium on top of the wage. Thus, the social discrimination introduced by the hukou system is partially compensated by the reactions of market participants, as migrant workers receive additional pay. Based on huge cross sections of private households, this paper provides insights into the size and the evolution of the wage premium. After controlling for standard wage determinants, such as sex, education, experience and ownership of firms, we find that the premium amounts to 7 percent of the hourly wage. Because of the premium, the share of non-wage labor costs is on the rise, especially for low-skilled migrants. To avoid further distortions and reduce inefficiencies, the hukou status should be unified. Migrants should obtain urban hukou as long as they live in cities. They should keep their land use rights when they are in the rural areas. Otherwise, the system could constitute a significant barrier for further urbanization. The removal of institutional bias could restore the link between wages and productivity and improve the allocation of labor.
Keywords: J30; R23; C23; 330; Chinese economic transformation; wage premium; hukou reform